Effectiveness of Open Access to Customer Financial Information for Tax Interests in Denpasar - Eka Krisna Putri, Dewa Ayu; Kurniawan, I Gede Agus (Fakultas Syariah INSURI Ponorogo, 2023)
Taxpayer compliance problems in Indonesia are still occurring as reflected in the compliance ratio which has not reached the maximum percentage. This condition prompted the government to stipulate Law Number 9 of 2017 concerning Access to Financial Information for Tax Purposes in the hope that taxpayers will not be absent from paying taxes. However, the enactment of this law has interesting pros and cons to study, how effective it is in supporting taxation interests in Indonesia and in Denpasar, Bali in particular. This research is empirical study with a fact approach. Data collection techniques were carried out by interviewing the head of the DJP for the Bali region, the Head of the Lmats Consulting Tax Consulting Office, and the taxpayers. The results of this study indicate that the implementation of Law No. 9 of 2017 concerning Access to Financial Information for Tax Purposes has been going well. The supporting factor for the implementation of Law No. 9 of 2017 is the support from the DPR and the ministries which led to the passing of Law No. 9 of 2017. The inhibiting factor for the implementation of Law No. 9 of 2017 is the limited number of IT staff at DGT and also banking which causes technical problems related to the reporting of financial data, besides that the lack of quantity of human resources owned by DGT, especially in the IT field, causes implementation to be disrupted. Based on the data obtained regarding the ratio of taxpayer compliance in Indonesia during the period 2017 to 2021, it was found that there was a significant increase in taxpayer compliance. This increase in taxpayer compliance indicates that the implementation of Law No. 9 of 2017 in Indonesia has been effective in increasing taxpayer compliance.